Producer mobility support in information-centric networks: research background and open issues. (29th March 2022) - Abrar, Ahmad; Arif, Ahmad Suki Che Mohamed; Zaini, Khuzairi Mohd
In recent times, an interesting innovation of information-centric networking (ICN) architecture has been introduced to replace the old fashion host-centric communication architecture with content-centric architecture. With the instant growth of mobile devices and mobile data traffic, the mobility issue in the current IP-based network is growing rapidly and is facing many inefficiencies such as unsupported mobility and data delivery. The unsupported mobility causes failure of the communication system and inaccessibility in the network services. The unsupported mobility stimulates several complications and issues in the network such as unavailability of content, denial of service, interest packets loss, and excessive burden in the network. Further, unsupported mobility affects the routing and forwarding plane in the network and terminates the content transmission to its consumers. Thus, this paper will critically explore this issue. It will present a strong foundation of the producer mobility support architecture, research challenges, previous solutions, and open research issues. Along with this discussion, a research roadmap will be delineated.